Solitary fibrous tumor of the pancreas: Analysis of 9 cases with literature review - ŞAHİN ÖZKAN, HÜLYA; BAĞCI ÇULÇİ, PELİN (My University, 2023)
Solitary fibrous tumor (SFT) has been increasingly reported in various anatomic sites. However, it is still extremely rare in the pancreas. Herein, we present the first series of primary pancreatic SFTs. Nine cases of primary pancreatic SFTs were analyzed. The mean age was 60 years (36 to 76 y) with no sex predilection. Six tumors were in the head, 3 were in the tail. On imaging studies, tumors were described as a hypervascular mass, 2 revealed cystic areas, and 3 were favored to be neuroendocrine tumors. On biopsy, 2 cases were diagnosed as atypical spindle cell tumor; one was misdiagnosed as suspicious for sarcoma, and another case as metastatic renal cell carcinoma. Two were diagnosed as low-grade sarcoma and low-grade stromal tumor on frozen sections. Grossly, tumors were well-demarcated with a median size of 4 cm (0.9 to 15 cm). Microscopically, they were composed of ovoid to spindle tumor cells with no significant mitotic activity and were arranged in alternating hypercellular and hypocellular areas. Staghorn-like vessels and entrapped pancreatic parenchyma were also detected within all tumors. Tumor cells revealed diffuse/strong nuclear STAT6 expression in 7 of 8, CD34 in 7 of 9, and bcl-2 in 4 of 4 tested cases. One tested tumor harbored NAB2-STAT6 fusion. Eight patients with available follow-up data were free of disease at a mean follow-up of 76 months (3 to 189 mo). SFT should be considered in the differential diagnoses of mesenchymal neoplasms of the pancreas. Immunohistochemical nuclear STAT6 expression is a characteristic feature of SFT. Primary pancreatic SFTs seem to have favorable biological behavior in our series.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Temel Bilimler; Medicine; Surgery Medicine Sciences; Pathology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; CERRAHİ; PATOLOJİ; ANATOMİ VE MORFOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; SURGERY; PATHOLOGY; ANATOMY & MORPHOLOGY; Cerrahi; Patoloji ve Adli Tıp; Anatomy; Surgery; Pathology and Forensic Medicine; mesenchymal tumor; pancreas; pancreatic; solitary fibrous tumor